Karakteristik penderita katarak senilis yang dilakukan tindakan pembedahan katarak di RSUP H. Adam Malik Medan tahun 2012 - Safriati Eka; Delfi dr; D Sihotang Aslim (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Background : Cataracts are a cloudiness in the lens. The WHO defines cataracts as a keen eyesight is less than 3/60 which is a cause of blindness worldwide. Cataract surgery is one of the important management against a significant lens cloudiness affects vision.1,2Objective : To know the characteristics of the patients with senile cataract who performed cataract surgery based on age and gender of the most incisive, sharp vision cataract the average pre operation, sharp vision average post surgery, systemic disease history, the use of companion planting and lens power lens planting an average of cataract surgery, the type most used on patients with cataract surgery is performed by 2012.Methods: This is a descriptive retrospective observational study on senile cataract sufferers who performed cataract surgery in the Hospital of Haji Adam Malik, Medan from January 2011 to December 2012 and control routine post-operative week VIII until 2012.Results : Of the total samples there are 152 samples sufferers cataract senilis done surgically, age most be found at age 60- 69 year namely 73 people (48%). Man 89 people (58.5% ), women 63 (41.4%), sharp of sight average pre operation most 1/300 for 48 people (31.5%), systemic disease history companion most is diabetes mellitus that is, (43.4%), discharging lens cropping (92.1%) and strength lens cropping average is 20.00D (23.5%), sharp of sight after operation <6/18-6/60 60 samples (39.4%), type surgically cataract most used is ECCE, 118 samples (77.6%).Conclusion : From an examination of the senile cataract sufferers sample 152 performed cataract surgery in 2012 found the largest age group 60-69 years of age, male gender more than women and sharp vision on average pre-operation is 1/300 and have a history of systemic disease of most Companion is diabetes mellitus. Sufferers who performed surgery on average using the lens with the lens power plant the largest planting was 20 D. Sharp vision under average operating <6/18-6/60, the type of cataract surgery is the most used is the ECCE.Keywords : senile cataract; cataract surgery; sharp vision pre operation; sharp vision post surgery; systemic diseas